Evaluating a handheld decision support device in pediatric intensive care settings. Issue 1 (4th January 2019) - Reynolds, Tera L; DeLucia, Patricia R; Esquibel, Karen A; Gage, Todd; Wheeler, Noah J; Randell, J Adam; Stevenson, James G; Zheng, Kai
Abstract: Objective: To evaluate end-user acceptance and the effect of a commercial handheld decision support device in pediatric intensive care settings. The technology, pac2, was designed to assist nurses in calculating medication dose volumes and infusion rates at the bedside. Materials and Methods: The devices, manufactured by InformMed Inc., were deployed in the pediatric and neonatal intensive care units in 2 health systems. This mixed methods study assessed end-user acceptance, as well as pac2's effect on the cognitive load associated with bedside dose calculations and the rate of administration errors. Towards this end, data were collected in both pre- and postimplementation phases, including through ethnographic observations, semistructured interviews, and surveys. Results: Although participants desired a handheld decision support tool such as pac2, their use of pac2 was limited. The nature of the critical care environment, nurses' risk perceptions, and the usability of the technology emerged as major barriers to use. Data did not reveal significant differences in cognitive load or administration errors after pac2 was deployed. Discussion and Conclusion: Despite its potential for reducing adverse medication events, the commercial standalone device evaluated in the study was not used by the nursing participants and thus had very limited effect. Our results have implications for the development and deployment of similar mobile decision support technologies. For example, they suggest that integrating the technology into hospitals' existing IT infrastructure and employing targeted implementation strategies may facilitate nurse acceptance. Ultimately, the usability of the design will be essential to reaping any potential benefits.